IMPLEMENTASI FRAMEWORK LARAVEL PADA APLIKASI PEMESANAN BARBERSHOP BERBASIS WEB (STUDI KASUS: MAIDEN BARBERROCK) - Andi Juandi, Muhammad Naufal Apriandi; Agung Susilo Yuda Irawan; Purwantoro (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
This study discusses the implementation of the Laravel framework in developing a web-based barbershop service booking application, with a case study at Maiden Barberrock. The background of this research is based on the need for a digital system that can simplify the service booking process to be faster and more organized. The manual system previously used was considered inefficient in managing schedules, transactions, and customer data. The development method used is agile scrum, which allows the system to be developed gradually through sprints. Each sprint has specific target features to be completed based on priority. Daily activities such as daily scrum are conducted to monitor progress and resolve any emerging issues. Laravel was chosen because it supports application development with a structured and secure approach using the model-view-controller (MVC) architecture. The application includes key features such as booking services based on time and barber, managing service and barber data by the admin, schedule validation, payment system, and booking history. To ensure the functionality works as expected, the system is tested using the blackbox testing method, which focuses on system input and output, and user acceptance testing (UAT) to assess how well the system meets user needs and is ready for use. With this system in place, the booking process at Maiden Barberrock becomes faster, more organized, and professional. The system also helps improve operational efficiency and customer satisfaction.